Whose geography? Which publics?. (March 2013) - Crampton, Jeremy W; Bowen, Jay; Cockayne, Daniel; Cook, Brittany; Nost, Eric; Shade, Lindsay; Sharp, Laura; Jacobsen, Malene
In this response, the members of a professional development graduate seminar at the University of Kentucky reflect on key implications and questions which arose from our reading of the Kitchin et al. (2013) paper. We found the paper very relevant to our situation as potential entrants to the academic labor market, and to practices of knowledge production and dissemination that we already face. We highlight the following three inter-related points: (1) The IrelandAfterNAMA (IAN) blog can be placed into a wider context of new (spatial) media developments; (2) the conception of "public geography" implied here is too narrow, focusing not on public participation, but on public reception of content, viewpoints and data. Thus we ask "which publics are being invoked?"; (3) the production and consumption of knowledge. We ask "whose geography?" We do not offer final answers to these questions, but rather pose them as an invitation to further dialogue.